PENGEMBANGAN MODUL PEMBELAJARAN PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT DENGAN PENDEKATAN CTL BERDASARKAN KURIKULUM 2013 - Shinta, Raddin Nur (Universitas Pendidikan Indonesia, 2014)
This study aims to develop a learning module addition and subtraction of integers with CTL approach that has been customized according to Johnson. Development model used in this study is the development model of Plomp is divided into five phases. The design of the development of this module will adopt until the fourth phase. The research instrument prepared in this study consisted of; (1) The questionnaire responses of experts and practitioners, (2) the student questionnaire, (3) observation sheets and questionnaires, (4) copies of the test. Subject of this research is the development of students in grade 4 in SDN 4 Malasan. Product development has met the criteria for a valid, practical, and effective. Validity of achievement percentage of 90, 46%. While the percentage of daily tests of completeness that is 82, 35%, and the percentage of student responses is 87, 5% and there is one subject that is not included. In terms of practicality, the average score validation result is 3, 6 (high criteria) and filling the questionnaire scores of observers, namely 3, 5 (high criterion). Keywords: modules, CTL, curriculum 2013.